Development of Creatorku Application for Managing Digital Influencer Portfolios using Lean Startup Approach - Tamiri, Muhammad Husni; Wahyuni, Elyza Gustri (Sistemasi: Jurnal Sistem Informasi, 2025)
Influencers face significant challenges in managing their digital portfolios to present analytics data professionally. Manual processes, such as taking screenshots and compiling data, which are time-consuming, often reduce work efficiency. This study develops the Creatorku application using the Lean Startup approach with the Build-Measure-Learn cycle to ensure the product meets user needs. The minimum viable product (MVP) includes data integration from Instagram and YouTube, an analytics dashboard, automatic portfolio creation, and a shareable link feature. Test results show that Creatorku completely eliminates the need for manual data management while enhancing professionalism in the eyes of partners. Additionally, the application supports influencer marketing by providing a solution that improves work efficiency and collaboration with brands. User feedback suggests integrating with other platforms, such as TikTok, improving data visualization, and adding personalization options. With these results, Creatorku is expected to become an innovative solution to support influencers and offer new insights for technology startups.